Provision of Education Services for Internally Displaced Persons in IDPs Camps in Nigeria: Challenges and Way Forward - Niyi Jacob Ogunode; Okwuagwu Esther Chijindu; Deborah Jegede (Researchparks Publishing, 2022)
In Nigeria, many internally displaced persons (children) in IDPs camps are not receiving quality education services because of many challenges. This paper examined the problems hindering the provision of education services for Internally Displaced Persons (children) in their various camps across Nigeria. Both qualitative and quantitative resources were sourced online and on print materials were used to provide empirical and opinion support to the various points raised in the paper. The paper concludes that inadequate funding, shortage of specialized and professional teachers, lack of modern infrastructural facilities, inadequate instructional materials, lack of data, corruption, poverty, limited school facilities and instructional challenges of internally displaced person (IDP) were the problems hindering the provision of education services for the Internally Displaced Persons (children) in IDPs camps in Nigeria. To ensure provision of quality education services in all IDPs camps across the federation, this paper advance the following suggestions; that the federal and state government should create a special funding programme for the education of the internally displaced persons in IDPs camps; federal government should direct the Minister of education to create the department of emergency education in the ministry of education to handle the education for internally displaced persons in IDPs camps across the country, government should develop an effective monitoring and evaluation system to check the financial allocation to all the internally displaced person camps to prevent diversion of funds, government should set up committee to ensure accurate data of school-aged children are collected in all IDPs camps to enable effective planning of education for the IDPs camps across the country etc.